Regional flood risk assessment via coupled fuzzy c-means clustering methods: an empirical analysis from China’s Huaihe River Basin - Wang, Zongzhi; Wu, Jingjing; Cheng, Liang; Liu, Kelin; Wei, Yi-Ming (Natural hazards (Dordrecht), 2018)
This study contributed to the comprehensive assessment of flood risk in the Huaihongnanpian flood control protected area (simplified as the HHNP) of the Huaihe River Basin in China. Flood risk analyses were performed by incorporating flood hazard and vulnerability. Flood hazard was simulated by a 1D–2D coupled hydrodynamic model. Flow velocity, inundation duration, and inundation depth were taken as hazard indicators, while agricultural population proportions, female population proportions, GDP per unit area, GDP per person, population density, residential density, shelter density, the land-use sensitivity index, road network density, and river network density were used as vulnerability indicators. Based on these indicators, a regional flood risk assessment model was put forward, which coupled fuzzy c -means clustering, factor analysis, and a clustering validity function. As an example, a proposed model was applied to evaluate the degree of flood risk for 15 townships in the HHNP. The research results showed that (1) flood risk in the HHNP was closely related to three main factors: socioeconomic factor, land cover factor, and flood factor; (2) the degree of risk was objectively divided into six zones: especially high, high, relatively high, medium, relatively low and low; and (3) in the 15 townships, Xiaobengbu (XB), Chengguan (CG), and Wuxiaojie (WX) fell into the especially high, high, and relatively high zones, respectively. Xinji (XJ), Toupu (TP), Daxin (DX), Caoguzhang (CGZ), Meiqiao (MQ), Caolaoji (CL), and Mohekou (MH) fell into the medium-risk zone. Linbeihuizu (LB) was categorized into the relatively low-risk zone, and Xinmaqiao (XM), Wangzhuang (WZ), Kuainan (KN), and Weizhuang (WZ) fell into the low-risk zone. The research results revealed the main driving factors and the spatial distribution of flood risk in the HHNP; therefore, it is highly significant for us to understand the main flood risk sources to provide guidance for flood control and management in the HHNP.